EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR ALJABAR LINEAR DENGAN MEMAMFAATKAN MATLAB - Silvia Harleni; Mardiana . (Institut Pendidikan Tapanuli Selatan, 2020)
Based on the researcher's experience when implementing the learning tools in STKIP Budidaya Binjai, student learning outcomes in the linear algebra course were still low. This study aims to determine the effectiveness of using the online jigsaw cooperative learning model on linear algebra learning outcomes by utilizing the Matlab software for STKIP Binjai Cultivation Students during the Covid-19 Pandemic. This type of research is a quasi-experimental. In the experimental class, it was treated using cooperative learning type jigsaw and the control class was given treatment using conventional learning then given a pretest and posttest. The Matlab program can be used as a tool in learning linear algebra without forgetting the importance of mastering concepts, theories, and procedures. The data in this study were analyzed using a simple regression test. The average score of students' mathematics learning outcomes in the experimental class before and after learning was 44.95 and 77.95. Meanwhile, the control class was 40.10 and 62.55. Based on these results, it is proven that the average mathematics learning outcomes of the experimental class are greater than the average control class. Likewise in hypothesis testing, the significance value or probability value = 0.008 <0.05 then H0 is rejected and Ha is accepted. This shows that there is an effective use of the jigsaw cooperative learning model on Linear Algebra learning outcomes by using matlab software for STKIP Budidaya Binjai students.